MODIFIKASI TUNGKU PEMBUATAN GULA AREN (Arenga Pinnata) MENGGUNAKAN BAHAN BAKAR LPG (Liquified Petroleum Gas) - Rizal Mokodompit; Ir. Freeke Pangkerego, MS; Dr. Ir. Lady Lengkey, MSi (Universitas Sam Ratulangi, 2018)
Abstract The purpose of this study was to modify and make furnace for the processing of palm sugar, test the performance of modified furnace and traditional furnace in terms of fuel usage and processing time, and calculate the efficiency of traditional furnaces and furnaces. The results showed that the processing of palm sugar sap using 3.6 kg LPG fuel modification furnace had a processing time of 3.33 hours whereas, the processing of traditional palm sugar palm sap using wood fuel as much as 49.3 kg had a processing time of 1, 73 hours because palm sugar has been preheated. The FCR fuel consumption rate using a modified furnace is 1,081 (kg / hour), and the FCR fuel consumption rate (fuel consumption rate) using traditional furnace is 28.49 (kg / hour). The efficiency of the modified furnace is 8.90%, and the efficiency of traditional furnaces is 1.07% Keywords: Processing Time, Fuel Consumption, Furnace Efficiency